Topology design of switched enterprise networks using a fuzzy simulated evolution algorithm - Youssef, H. (2020)
Abstract The topology design of switched enterprise networks (SENs) is a hard constrained combinatorial optimization problem. The problem consists of deciding the number, types, and locations of the network active elements (hubs, switches, and routers), as well as the links and their capacities. Several conflicting objectives such as monetary cost, network delay, and maximum number of hops have to be optimized to achieve a desirable solution. Further, many of the desirable features of a network topology can best be expressed in linguistic terms, which is the basis of fuzzy logic. In this paper, we present an approach based on Simulated Evolution algorithm for the design of SEN topology. The overall cost function has been developed using fuzzy logic. Several variants of the algorithm are proposed and compared together via simulation and experimental results are provided. r 2002 Elsevier Science Ltd. All rights reserved. Keywords: Enterprise networks; Simulated evolution; Fuzzy logic; NP-hard; Multiobjective optimization